Avaliação dos marcadores inflamatórios e do balanço redox durante o exercício físico, em indivíduos com insufiência cardíaca crônica - Giane Amorim Ribeiro Samora (2012)
Heart failure (HF) is a complex syndrome that results both in heart dysfunction and biochemical, neurohormonal, inflammatory and oxidative stress alterations. Inflammation and oxidative stress are related to the disease's pathogenesis and progression and contribute to the low functional capacity of these patients. The functional capacity assessment is of important clinical value, since it has prognostic information, gives data for physical exercise prescription and can be an indicator ofactivities of daily living. The 6-minute walking test (6'WT), the Human Activity Profile questionnaire (HAP) and the Cardiopulmonary Exercise Testing (CPET) are instruments that measure functional capacity directly or indirectly. Furthermore, physical exercise is recognized as an adjuvant therapeutic able to reduce the pathophysiological alterations of HF and promote an enhancement in quality of life. In this regard, the aimed of the first part of this study was to compare the effects of three exercises of different intensities and durations on the inflammatory markerssTNFR1 and IL-6 and on the oxidative stress (malondialdehyde- MDA and the activity of the antioxidant enzymes: catalase CAT and superoxide dismutase SOD) in individuals with chronic heart failure (HF). Methods: 18 patients with HF (45.4111.3 years old, left ventricular ejection fraction: 36.7 1 10.3%, NYHA l - III), performed three exercise sessions: M30 moderate intensity (60% VO2peak) for 30 minutes; L3O mild intensity (40% VO2peak) for 30 minutes and L45 - mild intensity for 45 minutes (lVl3O isocaloric). Blood analysis was performed before the exercise (baseline), immediately after (after) and 1 hour after the end of each session (after 1h), in order to determine sTNFR1, IL-6, IVIDA, CAT and SOD. Results: In M30 there was an increase of sTNFR1 and MDA immediately after exercise, followed by an increase of IL-6 and CAT after 1h. In L30, only an increase of IL-6 after exercise was observed and no significant alterations on the sTNFR1, IVIDA, CAT and SOD levels.As for exercise L45, there was an increase of MDA after exercise and of CAT after 1h, similar to what occurred for M30. Conclusions: The exercise intensity was a more determining factor for the physiological adjustments than the exercise duration. The moderate intensity exercise for 30 minutes (M30) promoted a larger stressor stimulus both pro-inflammatory and pro-oxidative, when compared to exercises L30 and L45. In response to this stressor stimulus, after 1h there was an anti-inflammatory action of IL-6 inhibiting the expression of TNF-oi, as well as the activation of the enzyme antioxidant system, expressed by the CAT increase. The second study aimed at assessing the HAP's validity in estimating the functional capacity of individuals with HF and its association with the variables related to functionality, such as distance walked in the 6'WT. Methods: 62 individuals with HF, average age of 47.98 x 10.84 years, NYHA classes I to Ill, performed a CPET andanswered the HAP questionnaire. On another day, they performed the 6'WT. The peak oxygen consumption (VO2peak) measured by CPET and the one estimated by the HAP as well as the distance walked on the 6'WT were assessed. The agreement between measured VO2peak versus estimated VO2peak was assessed by the Bland- Altman method. The concurrent validity of HAP with the distance walked on the 6'WTwas verified by linear regression analysis. Results: there was no agreement between measured VO2peak versus estimated VO2peak. The distance walked on the 6'WT showed a moderate association with the VO2peak of the HAP (r=0.62; p<0.0001). Conclusion: the estimation of VO2peak by the HAP did not agree with the gold standard measure of CPET. On the other hand, the HAP was moderately associatedto another functional capacity predictor, the 6'WT, and was able to differentiate the NYHA functional classes. It is, thus, a useful instrument to assess the functional state and limitation to physical exercise of these patients.